2004
DOI: 10.1105/tpc.016907
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana Dihydroxyacetone Phosphate Reductase Gene SUPPRESSOR OF FATTY ACID DESATURASE DEFICIENCY1 Is Required for Glycerolipid Metabolism and for the Activation of Systemic Acquired Resistance[W]

Abstract: Systemic acquired resistance (SAR) is a broad-spectrum resistance mechanism in plants that is activated in naive organs after exposure of another organ to a necrotizing pathogen. The organs manifesting SAR exhibit an increase in levels of salicylic acid (SA) and expression of the PATHOGENESIS-RELATED1 (PR1) gene. SA signaling is required for the manifestation of SAR. We demonstrate here that the Arabidopsis thaliana suppressor of fatty acid desaturase deficiency1 (sfd1) mutation compromises the SAR-conferred e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(153 citation statements)
references
References 58 publications
2
146
1
4
Order By: Relevance
“…Our earlier work has shown that a mutation in the SSI2-encoded S-ACP-DES affects many cellular responses in the plant, and we have demonstrated that the altered defense-related phenotypes in ssi2 plants are specifically associated with their low 18:1 levels (12,(15)(16)(17)22). Previous research by Nandi et al (37,38) has implicated a reduction in hexadecatrienoic acid (16:3) to be responsible for restoration of ssi2 phenotypes. However, several results contradict a role for 16:3.…”
Section: Discussionmentioning
confidence: 63%
“…Our earlier work has shown that a mutation in the SSI2-encoded S-ACP-DES affects many cellular responses in the plant, and we have demonstrated that the altered defense-related phenotypes in ssi2 plants are specifically associated with their low 18:1 levels (12,(15)(16)(17)22). Previous research by Nandi et al (37,38) has implicated a reduction in hexadecatrienoic acid (16:3) to be responsible for restoration of ssi2 phenotypes. However, several results contradict a role for 16:3.…”
Section: Discussionmentioning
confidence: 63%
“…Several specific findings are worth highlighting. First, SUPPRESSOR OF FATTY ACID DE-SATURASE 1 (SFD1), a dihydroxyacetone phosphate reductase that is involved in glycerolipid metabolism [42 ], and DEFECTIVE IN INDUCED RESIS-TANCE1 (DIR1), a putative lipid transfer protein [43], contribute to the establishment of systemic resistance. EDS1 and PAD4 are also necessary for the establishment of SAR (L Jorda, A Maldonado, J Parker, C Lamb, unpublished).…”
Section: The Lipid Linkmentioning
confidence: 99%
“…Wang et al (2009) have suggested that these two roles may be linked, as evidence exists for plant defense pathways being regulated by lipidbased signals (Nandi et al, 2004;Chandra-Shekara et al, 2007).…”
Section: Plastidial Ca Isoforms Have Multiple Functionsmentioning
confidence: 99%